The narrative of adventures and the Spanish Civil War: A reading of Os Imbatíveis em Salamanca by Manuela Moniz Lopes and Cremilde Madaíl - Ramos, Ana Margarida (2018)
Our purpose is to analyse one specific volume of a Portuguese book series for young readers called "Os Imbatíveis" and published in the nineties under the title Os Imbatíveis em Salamanca. In this book, a particular episode of the Spanish Civil War is turned into a fiction novel and a mystery case has to be solved by a group of friends. The heroes discover the family ties that link two of the characters and revisit the memory of that tragic historic event.